مصطلح السلوك واضطرابه بين علماء الشريعة وعلم النفس = The term al-Suluk (Behavior) and the confusion between shariah scholars and the psychologists = Perilaku dan kecelaruannya di kalangan ahli Shariah Islam dan psikologi - Jamud, Saif; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2018)
تُعد دراسةُ النفس البشرية وتحديد كنهها ودراسة ما ينتج عنها من سلوك من أبرز المسائل العلمية التي شغلت الجنس البشري، فمنذ العصور القديمة ويحاول العلماء والفلاسفة الخوض في الإجابة عن تساؤلات الإنسان عن نفسه، فكانت النتائج تظهر بحسب الزاوية التي ينظر الباحثون منها إلى نفس الإنسان، وقد تنوعت النظرة إلى مصطلح السلوك بوجه عام أو السلوك الإنساني بوجه خاص مما يجعل من ذلك مشكلة علمية ينبغي العناية بها، فقد أصبح من المهم بيان ما يعنيه مصطلح السلوك نفسه، ولإظهار القيمة الفارقة في نواتج دراسة السلوك بين الشريعة الإسلامية وعلم النفس، خصوصاً فيما يتعلق بفهم السلوك الموسوم بالاضطراب، لذا جاء هذا البحث ليقف على ما في كتب التراث الإسلامي من تعبير عن السلوك، وكيف تنظر الشريعة إلى المضطرب منه مقارنة بما عند علماء النفس، حيث تظهر نتائج هذا البحث أن مصطلح السلوك يحمل تعبيراً عاماً عن مطلق العمل الذي يصدر من قبل الانسان، أما فيما يتعلق بالاضطراب فقد ظهر في هذا البحث أن الشريعة الإسلامية لها تفصيلها الخاص المستند إلى الإطار التقييمي الشرعي من خلال الأحكام الشرعية في الدلالة على الاضطراب، مع استيعابها إطلاق مصطلح الاضطراب على السلوك الذي يتسم به ولو كان غير مخالف للتقييم الشرعي إذا ما وصفه علم النفس بذل ********************************************************** The study of human-self, the core of human existence and the behaviour which is generated from therein is considered to be one of the most important issues in which human beings have ever engaged. Philosophers and scientists have long been attempting to find out and answer the questions with respect to human selves. These attempts resulted in different findings according to the framework which was employed to study the subject matter. Attitude towards behavior-terminology in general and human behaviour in particular varies in a very diverse way which has put this issue as a problem where special focus needs to be carried out. It is crucial to identify the actual meaning of "behavior" and the differences in these two perspectives; the shariah and the psychology, especially when it comes to understanding the behavioral disorders. This piece of writing is an attempt to discover how traditional Islamic books dealt with the term "behavioral disorders" and how a disordered person was treated in comparison with the standpoint of psychologists in this regard. This study finds that the term "behavior" in traditional Islamic books has a general meaning that includes every action of humans, whereas the term "disorder" has its specific meaning based on the shariah framework and how it encompasses those behaviors as disorders which are prespribed so by psychologists and they are not in conflict with the shariah. ********************************************************* Kajian berkaitan diri manusia, teras kewujudannya dan perilaku yang terhasil dari dalam diri mereka merupakan antara isu yang pernah dibincangkan oleh para pengkaji. Ahli falsafah dan para saintis telah berusaha dari dahulu lagi untuk merungkai persoalan-persolan berkaitan manusia. Hasilnya, pelbagai jawapan yang berbeza telah didapati menerusi kerangka-kerangka kajian yang mereka gunakan. Respon terhadap terminologi tingkah laku secara umum dan perilaku manusia khususnya berbeza-beza menjadikan isu ini sebagai satu masalah di mana tumpuan khusus perlu dilakukan. Adalah penting untuk mengenal pasti maksud sebenar "tingkah laku" dan perbezaannya dari dua perspektif; Shariah dan psikologi, lebih-lebih lagi dalam memahami kecelaruan-kecelaruan tingkah laku. Kajian ini adalah bertujuan megetahui bagaimana buku-buku Muslim tradisional menjelaskan kecelaruan tingkah laku dan bagaimana ianya dirawat dalam perbandingannya dengan kaedah ahli psikologi. Kajian ini mendapati bahawa definisi tingkah laku dalam buku-buku Muslim tradisional adalah bersifat umum dimana ia merangkumi semua tindakan manusia manakala definisi kecelaruan bersifat khusus. Persoalannya bagaimana kecalaruan tersebut merangkumi kesemua tindakan manusia seperti yang difahami oleh ahli psikologi, dan dari perspektif Shariah ia bukan merupakan satu konflik.